Study of temperature changes in mineral fertiliser granules after contact with air in a granulation tower - Nadhem, Al-Khyatt Muhamad; Sklabinskyi, Vsevolod; Ostroha, Ruslan; Skydanenko, Maksym; Yukhymenko, Mykola; Bocko, Jozef; Ostroha, Denys; Zabitsky, Dmitry; Moskalchuk, Oleksii; Serhiienko, Andrii (Technology audit and production reserves, 2023)
The object of research is the process of granulation of nitrogen mineral fertilizers by the method of sprinkling. One of the most problematic areas is the lack of certainty regarding the dynamics of the temperature change of the granule when it is cooled by air in the granulation tower. The paper considers the process of urea granulation using a rotating vibrating granulator. The scheme of the rotating vibrating granulator as part of the experimental stand for granulating liquid urea is presented, the method of conducting experimental studies and the design parameters of the granulator are described. It is indicated that in the process of experimental research, the temperatures of the melt, granules and cooling air were recorded. It is emphasized that the contact of the cooling air with the flow of hot granules leads to a constant increase in air temperature due to the heat transferred from the granules, which makes it necessary to determine the final temperature of the air leaving the granulation tower. For this purpose, a mathematical model was developed and calculation equations were obtained to determine the temperature of the air in contact with the surface of the pellet and the temperature profile inside the pellet. Numerical calculations of the calculation equations made it possible to obtain temperature profiles of the granule along its radius. It is emphasized that the theoretically obtained temperature profile cannot be an accurate indicator of the real temperature of the pellet when it falls in the granulation tower. Analysis of the calculated results shows that the temperature of the granules in the lower part of the granulation tower is 60–62 °C. This temperature corresponds to the practically confirmed final temperature of the granule, which was measured on the experimental stand.